The effect of formal statistical courses attitudes on learning outcomes in a cohort of undergraduate dental students. (20th January 2021) - Chen, Fa; Hu, Zhijian; Yan, Lingjun; Lin, Zheng; Liu, Fengqiong; Lin, Lisong; Qiu, Yu; He, Baochang
Abstract: Introduction: Whilst statistical knowledge is essential for dental students' academic or professional careers, only a few studies have measured the attitudes of these students towards statistics courses. This study aimed to investigate the attitudes of a cohort of dental students towards a formal statistical course and explore the factors that are potentially related to these attitudes. Methods: A survey was performed amongst dental students of 2017 entry at Fujian Medical University, China. The questionnaire covers three aspects: demographic characteristics, educational background and attitudes towards formal statistics courses. Results: A total of 103 dental students enrolled for the survey, and the response rate was 100.0%. 44.7% of dental students had positive attitudes towards formal statistics courses with an overall average of 25.7 (SD = 2.2, out of 30). Students' computer skills, expectations of course achievement, attention in class and learning atmosphere of the class were significantly associated with the attitudes towards formal statistics courses. Moreover, students with positive attitudes experienced a greater improvement in the statistical cognition and application ability of statistical methods after the course than those with negative/neutral attitudes. Additionally, a positive correlation was observed between students' attitudes and achievement in the examination. Conclusion: These results suggest that attitudes are critical to the learning effectiveness in formal statistics courses amongst undergraduate dental students. All the educators involved should monitor the students' attitudes in the teaching process and make effective interventions to improve students' attitudes towards formal statistics courses.